Pengaturan Hukum Pidana terhadap Pelaku Pertambangan Ilegal di Indonesia - I Gede Sadia Dwi Ratmaja; I Putu Edi Rusmana (Wajah Hukum, 2025)
Illegal mining in Indonesia has become a serious issue with widespread environmental, economic, and social impacts. This study aims to analyze the criminal law regulations regarding illegal mining offenses and the sanctions imposed on perpetrators based on Indonesian positive law. The research method used is normative juridical, with a descriptive-analytical approach. The findings indicate that the primary regulation governing illegal mining offenses is Law Number 3 of 2020 on Mineral and Coal Mining (UU Minerba), which imposes a maximum prison sentence of 5 years and fines up to Rp100.000.000.000 (one hundred billion rupiah). Additionally, illegal mining activities causing environmental damage may be subject to additional sanctions under Law Number 32 of 2009 on Environmental Protection and Management and Law Number 18 of 2013 on the Prevention and Eradication of Forest Destruction. Although the regulations are clear, challenges in law enforcement remain a major obstacle. Therefore, synergy between the government, law enforcement agencies, and the community is needed to effectively eradicate illegal mining.